Answer:
x = 4
x = - 3
Explanation:
Method 1
Quadratic Formula
(3x + 9)(x - 4) = 0
3x(x - 4) + 9(x - 4) = 0
3x² - 12x + 9(x - 4) = 0
3x² - 12x + 9x - 36 = 0
3x² - 3x - 36 = 0
3(x² - x - 12) = 0
![(3(x^(2) - x - 12))/(3) = (0)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/z7gdddz4xny8n5knbgfhei4wfjbn1bes2t.png)
![x={\frac{-b±\sqrt{b^(2)-4ac } }{2a} }](https://img.qammunity.org/2022/formulas/mathematics/college/xd9dr1t6fmsu5zaewc0jrtkfuxfazl4dyt.png)
Ignore the A after the -b, wouldn't let me type it correctly. Ignore the A for the rest of the explanation as well.
x² - x - 12 = 0
a = 1
b = - 1
c = - 12
![x={\frac{-(-1)±\sqrt{(-1)^(2)-4(1(-12)) } }{2(1)} }](https://img.qammunity.org/2022/formulas/mathematics/college/mch6zu58tyqoe3zrhtrmjggectdbgrw9zk.png)
![x={(-(-1)±√(1-4(1(-12)) ) )/(2(1)) }](https://img.qammunity.org/2022/formulas/mathematics/college/f5yre04dq3uncoos27gpjm3ocbovbil4mj.png)
![x={(-(-1)±√(1+48 ) )/(2(1)) }](https://img.qammunity.org/2022/formulas/mathematics/college/xk8zc9vyxcueflag7u5way1kgorwrpz9yd.png)
![x={(-(-1)±√(49 ) )/(2(1)) }](https://img.qammunity.org/2022/formulas/mathematics/college/4er15y0abo874l01ri0xvnp6w5pz86lt8j.png)
![x={(1±7 )/(2(1)) }](https://img.qammunity.org/2022/formulas/mathematics/college/2dw8lrpmi9svztnmk8ntj8g8m9tf0377ca.png)
![x={(1±7 )/(2) }](https://img.qammunity.org/2022/formulas/mathematics/college/ujxz2qr9lp0hg0clgy0w0lok901uc4612f.png)
Separate into two equations.
One with addition and the other with subtraction.
![x={(1+7 )/(2) }](https://img.qammunity.org/2022/formulas/mathematics/college/d6gxbfknsokd50qmg787yvn2kaiwjzsxdl.png)
![x={(1-7 )/(2) }](https://img.qammunity.org/2022/formulas/mathematics/college/3hhskfxltsvj9yt4a7ir30f655yzqugj94.png)
x = 4
x = - 3
Method 2
Factors
(3x + 9)(x - 4) = 0
3x(x - 4) + 9(x - 4) = 0
3x² - 12x + 9(x - 4) = 0
3x² - 12x + 9x - 36 = 0
3x² - 3x - 36 = 0
3(x² - x - 12) = 0
3(x² + 3x - 4x - 12) = 0
3(x² + 3x + (- 4x - 12)) = 0
3(x(x + 3) - 4(x + 3)) = 0
3(x - 4)(x + 3) = 0
Create separate equations
x - 4 = 0
x + 3 = 0
x - 4 = 0 ⇒ x - 4 + 4 = 0 + 4 ⇒ x = 4
x + 3 = 0 ⇒ x + 3 - 3 = 0 - 3 ⇒ x = - 3
x = 4
x = - 3